2022
DOI: 10.3390/plants11131708
|View full text |Cite
|
Sign up to set email alerts
|

Seed Transmission of Pathogens: Non-Canonical Immune Response in Arabidopsis Germinating Seeds Compared to Early Seedlings against the Necrotrophic Fungus Alternaria brassicicola

Abstract: The transmission of seed-borne pathogens by the germinating seed is responsible for major crop diseases. The immune responses of the seed facing biotic invaders are poorly documented so far. The Arabidopsis thaliana/Alternaria brassicicola patho-system was used to describe at the transcription level the responses of germinating seeds and young seedling stages to infection by the necrotrophic fungus. RNA-seq analyses of healthy versus inoculated seeds at 3 days after sowing (DAS), stage of radicle emergence, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 83 publications
0
33
0
Order By: Relevance
“…Recent data from the compatible interaction Alternaria brassicicola-A. thaliana , used as seed transmission model, showed that host defense pathways are subjected to drastic changes during the germination process (Ortega-Cuadros et al, 2022). It would be interesting to explore whether such rearrangements take place in other compatible interactions such as Xcf -bean and if a link with epigenetic modifications exists.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from the compatible interaction Alternaria brassicicola-A. thaliana , used as seed transmission model, showed that host defense pathways are subjected to drastic changes during the germination process (Ortega-Cuadros et al, 2022). It would be interesting to explore whether such rearrangements take place in other compatible interactions such as Xcf -bean and if a link with epigenetic modifications exists.…”
Section: Discussionmentioning
confidence: 99%
“…However, the immune responses of seeds to biotic interactions during germination have been little studied, although this step is crucial to control seed-borne pathogen transmission to the new plant [21,24]. The model pathosystem Arabidopsis thaliana/Alternaria brassicicola has been recently used to describe gene regulation induced by the necrotrophic interaction during germination and seedling establishment [1,21,61].…”
Section: Interaction With the Necrotrophic Seedborne Fungi Alternaria...mentioning
confidence: 99%
“…They involve different physical barriers such as cell wall appositions, hormonal signaling and antimicrobial metabolites such as phytoalexins or reactive oxygen species (ROS) and proteins [13,14,19,20] (Figure 1b). Recent studies using the pathosystem Arabidopsis thaliana/Alternaria brassicicola [21] have described non-canonical defense responses in the germinating seeds 1 compared to the established model describing defense mechanism against a necrotrophic agent [20,22], most of which are based on the physiological model of rosette leaf inoculation [23]. This review addresses the specific features of germinating seeds in terms of their responses to necrotrophic attacks [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations